Factors influencing job preferences among undergraduates business students in Universiti Utara Malaysia - Rushda Adiba, Abdullah Sani (2020)
The purpose of this study is to examine the factors that final year undergraduates business students of Univesiti Utara Malaysia (UUM) consider important in selecting their first job after graduation. Salary and benefits, career development and job security have been chosen as the independent variables for present study. To investigate the job preferences of business students, 234 final year undergraduate business students from UUM were surveyed. Data then were analyzed using Statistical Package for the Social Sciences (SPSS) version 22.0 using Reliability Analysis, Correlation Analysis and Multiple Regression. The result showed only career development and job security were significantly positive with job preferences while salary and benefits was not significantly influence to job preferences. Besides that, research findings indicated career development was the strongest factor influence to job preferences followed by job security.